2020
DOI: 10.3389/fonc.2020.595793
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Importance of the Preoperative Naples Prognostic Score for Patients With Adenocarcinoma of the Esophagogastric Junction

Abstract: BackgroundThe naples prognostic score (NPS) is established according to nutritional or inflammatory state, and it is identified as the new prognostic score for a variety of malignant tumors. However, its significance in cases suffering from adenocarcinoma of esophagogastric junction (AEJ) who receive surgery remains unclear so far.MethodsIn this study, patients receiving surgery without preoperative therapy were examined between June 2007 and August 2017 in a retrospective way. Typically, the serum albumin lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…We have recently demonstrated that NPS is a powerful predictor of long-term survival both in colorectal- and gastric-cancer patients [ 32 , 33 ]. Subsequently, many independent studies from different parts of the world, have shown that NPS is significantly correlated with oncological outcome in several human tumors including lung, endometrial, pancreatic, and gastro-esophageal cancers [ 28 , 50 , 51 , 52 , 53 ]. This is not surprising because NPS includes the neutrophil-to-lymphocyte and the lymphocyte-to-monocyte ratios which have been shown to be reliable surrogate indicators of the host inflammatory and immunological status [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have recently demonstrated that NPS is a powerful predictor of long-term survival both in colorectal- and gastric-cancer patients [ 32 , 33 ]. Subsequently, many independent studies from different parts of the world, have shown that NPS is significantly correlated with oncological outcome in several human tumors including lung, endometrial, pancreatic, and gastro-esophageal cancers [ 28 , 50 , 51 , 52 , 53 ]. This is not surprising because NPS includes the neutrophil-to-lymphocyte and the lymphocyte-to-monocyte ratios which have been shown to be reliable surrogate indicators of the host inflammatory and immunological status [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cachexia, as a complex and multifactorial syndrome, affects about 50%-80% of cancer patients and is related to 20%-40% of cancer deaths (Freire et al, 2019). Multiple nutritional assessment systems, including Naples Prognostic Score (NPS), Nutritional Risk Screening (NRS), body mass index (BMI), albumin (ALB), and prognostic nutritional index (PNI), have emerged with the aim of detecting and predicting the clinical outcomes of gastric cancer patients (Li et al, 2019;Wu et al, 2019;Bae, 2020;Park et al, 2020;Xiong et al, 2020). It is also reported that immunological status is associated with the patient's prognosis (Sato et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, the creator of the scoring system said that patients with the worst Naples prognostic score experienced more postoperative complications, and our study does not support this conclusion [ 18 ]. Similarly, two of the subsequently published articles had the same conclusions as ours [ 20 , 21 ], and the remaining articles did not list data related to postoperative morbidity [ 19 , 22 25 ]. This finding may be related to the careful supervision and continuous maintenance of the patient’s immune-nutritional status by attending physicians during hospitalization.…”
Section: Discussionmentioning
confidence: 74%
“…Most recently, a novel multidimensional comprehensive prognostic evaluation system, the Naples prognostic score (NPS), was established based on albumin, total cholesterol, NLR, and lymphocyte-monocyte ratio (LMR) although a prospective clinical trial [18]. This scoring system has been reported in oesophageal cancer, lung cancer, pancreatic cancer, colorectal cancer, endometrial cancer, osteosarcoma, and gastric cancer, which is of great significance [19][20][21][22][23][24][25]. However, the role of NPS in patients with GISTs remains unclear.…”
Section: Introductionmentioning
confidence: 99%